The literary development of MT 1Kings 8:1–11 in light of the Septuagint - Chike, Julian C. (Textus, 2019)
The literary development of the book of Kings continues to occasion much debate, including the long narrative of Solomon’s temple dedication in 1Kings 8. The quest for clarity may be aided by the textual witness of the Old Greek (OG). This study analyzes the textual relation between MT-1Kgs 8:1–11 and OG-3Kgdms 8:1–11 to discern the literary development of MT in light of the shorter version preserved in OG. I argue that the OG translator is not the source of the textual discrepancy; rather the MT reflects an expanded version of the OG Hebrew Vorlage. As the additional material evinces the influence of both Priestly and Deuteronomistic style, I suggest the literary growth exhibited in 1Kgs 8:1–11 occurred during the Persian period when a Deuteronomistic-Priestly school sought to combine the Deuteronomistic History with Genesis–Numbers.